Percorsi di valutazione partecipata nei gruppi dei genitori per il sostegno alla genitorialità - Sirtoli, Sara; Serbati, Sara (Rivista Italiana di Educazione Familiare, 2017)
The study focuses on a Research carried out within P.I.P.P.I National Programme, (Programme of Intervention for Prevention of Institutionalization), launched in 2010 by the Italian Ministry of Welfare in collaboration with University of Padua. In that context, the parents’ group for the parenting support is realized as one of the main interventions. The study aims to evaluate if parents’ group activities allow to change the perceptions of participants’ about their parenting styles. The instruments (Protective Factor Scale – PFS – and parents’interviewing) realized a participative and transformative evaluation path, and they are used also in order to promote parents’ reflections on their changes. The otucomes show a change in parents’ perceptions. In the Conclusions, they are considered the contributions to the study by the parents involved, as main actors of their own evaluation.